A household survey on screening practices of household contacts of smear positive tuberculosis patients in Vietnam. - Thanh, T; Ngoc, S; Viet, N; Van, H; Horby, P; Cobelens, F; Wertheim, H (BioMed Central, 2014)
BACKGROUND: Close contacts of tuberculosis (TB) patients are at increased risk of developing tuberculosis. Although passive contact screening guidelines are incorporated in the national TB control program, currently it is unknown how frequent close contacts are screened for TB in Vietnam. This study assesses current contact screening practices in Vietnam and determines the proportion of household contacts screened of newly registered TB patients. METHOD: Survey of household contacts of smear-positive TB patients (index patients) registered for treatment in 2008 in three Vietnamese cities. Households were interviewed in 2010 about screening for TB since treatment registration date of the index patient. RESULTS: We interviewed 4,118 household contacts of 1,091 identified index cases. Contact screening mainly relied on self-referral by household contacts. Of the 4,118 household contacts, 474 (11.5%) self-referred for TB screening, while this screening proportion was only 5.5% among contacts under 5 years old (16/293). Sputum examinations were performed in 374 (78.9%) of the screened contacts. Contact screening identified 27 cases of pulmonary TB (0.7%; or 656 cases/100,000 contacts), of which 20 were detected by sputum smear. CONCLUSIONS: The low proportion of household TB contacts screened for TB illustrates the limitations of passive contact screening as currently practiced in Vietnam. Children under 5 years of age are particularly neglected with this approach. Active contact screening with fixed follow-up times of close contacts of newly diagnosed TB patients should be considered in Vietnam, particularly in case of young children and drug-resistant TB.